Faktor yang mempengaruhi ibu menyapih anak di bawah usia 2 tahun - Rika Yulendasari; Sumbara Sumbara; Redia Indira Putrianti (Holistik Jurnal Kesehatan, 2020)
Practices of breastfeeding and weaning among mothers of children under 2 years old at Bandar Lampung-Indonesia Background: Weaning is a process for stopping breastfeeding gradually or at once. This process can be either because of the child herself wanting to stop breastfeeding or because the mothers desire, or by both of them for many reasons. Data from survey of health demography in Indonesia  in 2017 showed that there were only 54.6% of children were receiving breastfeeding complete until 2 years old.Purpose: Know the factors of practices of breastfeeding and weaning among mothers of children under 2 years oldMethods: A quantitative research by using Cross Sectional approach. Population was all mothers who has children under two years old. Samples were 145 respondents. Data were collected by using questionnaires and anthropometry. Data were analyzed by using Chi-Square Test.Results: There were correlations of occupation (p-value 0.025 < α 0.05) and OR = 2.7, nutrition status (p-value 0.006 < α 0.05) and OR=3.5, and family support (p-value 0.002 < α 0.05) and OR= 3.1 on practices of breastfeeding and weaning among mothers of children under 2 years oldConclusion: There were practices of breastfeeding and weaning among mothers of children under 2 years old. Suggestion to health worker and provider to improve health services especially promotion program and education for essential  of breastfeeding until the children complete 2 years old.Keywords: Practices; Breastfeeding; Weaning; Mothers; Children under 2 years old.Pendahuluan: Menyapih adalah proses berhentinya masa menyusui berangsur-angsur atau sekaligus. Proses itu dapat disebabkan oleh si anak itu sendiri untuk berhenti menyusu atau bisa juga dari sang ibu untuk berhenti menyusui anaknya, atau keduanya dengan berbagai alasan.Berdasarkan data dari Survey Demografi Kesehatan Indonesia (SDKI) di tahun 2017, presentase anak yang mendapatkan ASI sampai usia  2 tahun  hanya sebesar 54,6%.Tujuan: Diketahui faktor - faktor  yang  mempengaruhi ibu menyapih   anak di bawah usia  2 tahun.Metode: Penelitian kuantitatif dengan pendekatan cross sectional. Populasi pada penelitian ini adalah semua ibu yang memiliki anak di bawah usia 2 tahun. Sampel dalam penelitian ini sebesar 145 responden. Instrumen dalam penelitian ini dengan menggunakan lembar kuesioner dan antropometri. Uji statistik yang digunakan adalah  uji Chi-Square.Hasil: Terdapat hubungan pekerjaan dengan penyapihan pada anak dibawah usia 2 tahun (p-value = 0,025 < α = 0,05) serta nilai OR= 2,7, status gizi  (p-value = 0,006 < α = 0,05) nilai OR = 3,5, dan dukungan keluarga (p-value = 0,002 < α = 0,05) dan nilai OR=3,1.                                 Simpulan: Ada hubungan pekerjaan, status gizi, dan dukungan keluarga dengan penyapihan pada anak dibawah usia 2 tahun. Saran bagi petugas kesehatan untuk meningkatkan pelayanan dan memberikan penyuluhan terhadap ibu menyusui mengenai pentingnya pemberian ASI samapai usia anak 2 tahun.